Restored Through Learning: Hugh of St. Victor’s Vision for Higher Education - Halverson, James L. (Christian scholar's review, 2011)
In the past two decades the evangelical academy has devoted a good deal of attention to the “Christian scholar” and “Christian scholarship.” While these discussions have born considerable fruit, they lack the scope to cast a vision for Christian higher education in general. Jim Halverson argues that the Christian academy needs to articulate a vision for Christian learning that encompasses all members of and stakeholders in Christian instructions of higher education. Since this is not the first time the Christian academy has confronted such a task, the author urges us to look at the educational theories of Hugh of St. Victor, a twelfth-century scholar and teacher, as a suggestive template upon which to build such a vision.